2019
DOI: 10.1080/03906701.2019.1641276
|View full text |Cite
|
Sign up to set email alerts
|

School segregation: institutional rules, spatial constraints and households’ agency

Abstract: School segregation' indicates the concentration of a minority into a school that significantly exceeds the presence of the same population living in the surrounding territory. A segregated school is generally synonymous of low level of attainment and social marginalization. This phenomenon can be addressed as an urban issue or an educational problem, studied through spatial measures or qualitative interviews, interpreted as an institutional or a spatial effect. Many disciplines and approaches have in fact addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Empirical evidence has shown that far from achieving their goals, school choice reforms have exacerbated educational inequality in several respects (Cordini 2019). In the Swedish context, for example, studies indicate that ethnic school segregation increased after the reform was implemented (Böhlmark, Holmlund, and Lindahl 2015;National Agency for Education 2012).…”
Section: School Choice and School Segregationmentioning
confidence: 99%
“…Empirical evidence has shown that far from achieving their goals, school choice reforms have exacerbated educational inequality in several respects (Cordini 2019). In the Swedish context, for example, studies indicate that ethnic school segregation increased after the reform was implemented (Böhlmark, Holmlund, and Lindahl 2015;National Agency for Education 2012).…”
Section: School Choice and School Segregationmentioning
confidence: 99%